2016
DOI: 10.1177/0192623316678931
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Multiorgan Initiation–Promotion Assay for Chemical Carcinogenesis in the Wistar Rat

Abstract: The medium-term multiorgan initiation-promotion chemical bioassay (diethylnitrosamine, methyl-nitrosourea, butyl-hydroxybutylnitrosamine, dihydroxypropylnitrosamine, dimethylhydrazine [DMBDD]) with the Fischer 344 rat was proposed as an alternative to the conventional 2-year carcinogenesis bioassay for regulatory purposes. The acronym DMBDD stands for the names of five genotoxic agents used for initiation of multiorgan carcinogenesis. The Brazilian Agency for the Environment officially recognized a variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…By employing the CHAT tool and comparing the cancer hallmarks profiles of B[ a ]P and crystalline silica, we hypothesize that in a co-exposure setting, these chemicals could cause carcinogenic synergies. They may act in accordance with experimental studies employing initiation–promotion protocols ( Cohen and Ellwein 1990 ; Solano et al. 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…By employing the CHAT tool and comparing the cancer hallmarks profiles of B[ a ]P and crystalline silica, we hypothesize that in a co-exposure setting, these chemicals could cause carcinogenic synergies. They may act in accordance with experimental studies employing initiation–promotion protocols ( Cohen and Ellwein 1990 ; Solano et al. 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address these challenges, researchers have developed multi-organ carcinogenesis models over the years, aiming to replicate real-world exposure to carcinogens and investigate the impact of environmental chemicals on cancer development across various organs within a single experimental framework. These models operate on the initiationpromotion concept of chemical carcinogenesis, employing multiple initiator carcinogens to evaluate the potential of environmental chemicals in promoting cancer development across multiple organs [16][17][18][19]. For instance, studies have demonstrated that the combined administration of N-nitroso diethylamine (NDEA) and azoxymethane (AOM) to initiate both liver and colon carcinogenesis results in more severe preneoplastic lesions in the liver compared to NDEA treatment alone [20].…”
Section: Introductionmentioning
confidence: 99%